Survival status of young plantations in Parbat district, Nepal - Paudel, G.; Acharya, R. (Banko Janakari, 2018)
In Nepal, a lot of resources have been invested for establishing plantations. Due to lack of assessment of the survival status of planted seedlings, we have inadequate information about how many successful plantations that we have established in the country. This study was carried out in fourteen community forests (CFs) of Parbat district with the aim of analyzing survival status of the planted seedlings. Plantation was done in June/July 2015 and total count of the seedlings was done in June 2016. In the studied CFs, eleven species were planted comprising 20,172 seedlings in which 58.57% seedlings were survived at the end of first year. The cause of seedling mortality was identified through observation, judgment and interaction with local people. The main causes of seedling mortality (52%) were due to small size and unhealthy seedlings, lack of care during transportation and handling. Forest fire, weeds, drought, disease and grazing were found to be responsible for the mortality of 17%, 12%, 10%, 7% and 2% seedlings, respectively. Regular monitoring of plantation area with the involvement of local community members is recommended for policy makers and assessment of survival rate of different species in different ecological regions is recommended for researchers. Banko Janakari A Journal of Forestry Information for Nepal Special Issue No. 4, 2018, Page : 21-26